2013
DOI: 10.1186/1478-811x-11-71
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of the C. elegans Kinome identifies Kinases required for normal protein Homeostasis, Mitochondrial network structure, and Sarcomere structure in muscle

Abstract: BackgroundKinases are important signalling molecules for modulating cellular processes and major targets of drug discovery programs. However, functional information for roughly half the human kinome is lacking. We conducted three kinome wide, >90%, RNAi screens and epistasis testing of some identified kinases against known intramuscular signalling systems to increase the functional annotation of the C. elegans kinome and expand our understanding of kinome influence upon muscle protein degradation.Results96 kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 48 publications
(90 reference statements)
4
37
0
Order By: Relevance
“…By comparing the developmental phenotypes, such as growth or uncoordinated movement observed in this study to developmental phenotypes observed in RNAi experiments by other investigators using the same RNAi bacteria clone, a potential discrepancy of RNAi results for 17% of total genes screened was identified. This is in concordance with published RNAi screens17, 20 and half of these potential discrepancies are cases in which we identified a developmental phenotype in response to RNAi but for which a wild‐type phenotype was observed in RNAi experiments by others, indicating that either the RNAi was more effective in this study and therefore these results may be new findings, or these results are false positives. This is again consistent with published RNAi screens17, 20 and most likely represents our method producing a first discovery of function rate that is higher than past studies.…”
Section: Methodssupporting
confidence: 92%
See 4 more Smart Citations
“…By comparing the developmental phenotypes, such as growth or uncoordinated movement observed in this study to developmental phenotypes observed in RNAi experiments by other investigators using the same RNAi bacteria clone, a potential discrepancy of RNAi results for 17% of total genes screened was identified. This is in concordance with published RNAi screens17, 20 and half of these potential discrepancies are cases in which we identified a developmental phenotype in response to RNAi but for which a wild‐type phenotype was observed in RNAi experiments by others, indicating that either the RNAi was more effective in this study and therefore these results may be new findings, or these results are false positives. This is again consistent with published RNAi screens17, 20 and most likely represents our method producing a first discovery of function rate that is higher than past studies.…”
Section: Methodssupporting
confidence: 92%
“…Quality control of our RNAi screens was as previously described and diagrammed for the RNAi screen of the C. elegans kinome requirement for a muscle 20. By comparing the developmental phenotypes, such as growth or uncoordinated movement observed in this study to developmental phenotypes observed in RNAi experiments by other investigators using the same RNAi bacteria clone, a potential discrepancy of RNAi results for 17% of total genes screened was identified.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations